PENGGUNAAN MODEL WORDSQUARE DALAM MENINGKATKAN HASIL BELAJAR PKN DI KELAS IV - Herawati, Ida; Salimi, Asmayani; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrak General purpose of research to improve student learning outcomes through wordsquare model. Descriptive Method in the form of Classroom Action Research, is collaborative. Data collection techniques used are the technique of direct observation and measurement by means of data collection is the Student Worksheet. Setting research with the subject of Teachers / Researchers and students of class IV amounted to 33 students.1) The ability of teachers planning learning wordsquare model experienced an average increase of 0.35 with an average value of 3.64. 2) The ability of teachers to implement learning model wordsquare experienced an average increase of 0.28 with an average value of 3.55. 3) Students' learning outcomes of the wordsquare model experienced an increase in cycles of 8.30 with an average score of 65.04. Conclusion and suggestion: the use of wordsquare model in learning Citizenship Education can improve student learning outcomes, teachers are expected to use wordsquare model in improving student learning outcomes in the futureÂ Keywords: Learning outcomes, Wordsquare Model, Citizenship Education.